Family life stress, maternal depression and child behavioral health in industrialized Italian cities. (30th September 2020) - Bansal, E; Renzetti, S; Xhani, N; Cagna, G; Conversano, M; Patrono, A; Claudio, L; Lucchini, R; Placidi, D
Abstract: Although family life stress adversely impacts child health, few tools measure its relationship to child outcomes in the setting of maternal variables. This study validates the Italian version of Crisis in Family Systems-Revised (CRISYS-R) and characterizes relationships between family life stress, maternal depression and child behavior in two Italian cities. This cross-sectional study was nested in current research on health impacts of neurotoxic environmental exposures in children. 101 mother-child pairs (child age=9.91±2.17yrs; 53% female) and children's teachers were enrolled in Taranto (south Italy) and Brescia (north Italy). Mothers performed the Italian CRISYS-R and PHQ9; teachers completed Child Behavior Checklist (CBCL/6-18). Spearman's rank correlation coefficients showed associations of family CRISYS-R, maternal PHQ9 and child CBCL/6-18. Wilcoxon Rank-Sum test compared groups of continuous variables. Mothers with depressive symptoms (PHQ9≥5) reported higher ongoing stress and proportion of negative stressors on CRISYS-R than non-depressed mothers (p < 0.05). Children of depressed mothers performed worse in all CBCL/6-18 domains: Internalizing Problems, Externalizing Problems and Total Problems (p < 0.01). Specifically, children of depressed mothers scored higher on subscales of Anxious-Depressed (p < 0.05), Withdrawn-Depressed (p < 0.01), Rule-Breaking (p < 0.01) and Aggressive Behavior (p < 0.05). Maternal depressive symptoms correlated with ongoing stress (rs = 0.27; p < 0.01), child Internalizing Problems (rs = 0.34; p < 0.001), Externalizing Problems (rs = 0.28; p < 0.01) and Total Problems (rs = 0.35; p < 0.001). This study describes links among maternal depression, family life stress, and child behavioral health. It is first to validate Italian CRISYS-R and to explore these factors conjointly in Italian contexts with known neurotoxic exposures. Findings support considering maternal depression and family life stress in child behavioral and environmental health research and policy. Key messages: Family life stress, maternal depressive symptoms, and preadolescent behavioral health were highly interrelated in two industrialized Italian cities. The Italian version of CRISYS-R is a useful instrument for assessing and understanding family life stress, a crucial yet under-explored contributor to child behavioral health outcomes.